Sistem Penatausahaan Barang Milik Daerah (BMD) Berdasarkan Permendagri Nomor 47 Tahun 2021 Pada BPKADP - Josua Averindo; Dokman Marulitua Situmorang; Frengky Situmorang; Alexander Mario Retto Djong; Belia Mulyaningtyas (Politeknik Ganesha Medan, 2025)
regional assets in accordance with applicable laws and regulations. This paper presents an analysis of the process of implementing regional asset administration at the Regional Financial and Asset Management Agency of the Muara Enim Regency Government. The purpose of this analysis is to understand the process of implementing regional asset administration at the Regional Financial and Asset Management Agency of the Muara Enim Regency Government. The data collection methods used in the preparation of this final assignment include library research and field studies through interviews with the Head of the Asset Administration Sub-Division and staff under the asset administration at the Regional Financial and Asset Management Agency of the Muara Enim Regency Government. The results of this research demonstrate that the administration of regional assets at the Regional Financial and Asset Management Agency of the Muara Enim Regency Government aligns with Minister of Home Affairs Regulation Number 47 of 2021 concerning Procedures for the Implementation of Bookkeeping, Inventory, and Reporting of Regional Assets.